PERMAINAN TRADISIONAL UNTUK MENINGKATAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IVB SD KATOLIK MAUMERE 2 - MARIA GAUDENSIANA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The background of this study is the low student learning outcomes, especially in Mathematics Subjects. The purpose of this study was to describe the application of traditional game strategies to be able to improve mathematics learning outcomes in IVB grade students in Maumere Catholic Elementary School 2. The subjects of this study were students in Maumere Catholic Elementary School 2. This research was a Classroom Action Research which lasted for two cycles consisting of planning, action, observation and reflection. Data collection techniques in this study were student evaluation questions consisting of 6 multiple choice questions and 4 descriptions to determine student learning outcomes and were supported by observation. The implementation of the action produced results, in the form of an increase in the learning outcomes of students in grade IVB at Maumere Catholic Catholic Elementary School 2 with a total of 20 students. In the first cycle students who completed the KKM as many as 9 students or 45% and 11 students who did not complete or 55% with an average grade of 69.64; in the second cycle that completed as many as 20 students or 100% and an average class of 90. By looking at the results of the two cycles above it can be concluded that the use of the Traditional Game strategy can improve student learning outcomes in mathematics subject matter flat build